Pelatihan Pengurusan Jenazah (Tajhiz Al-Mayyit) Kepada Masyarakat Desa Binaan Universitas Malikussaleh - Zarkasyi, Zarkasyi; Muttakin, Muttakin; Fitriani, Henni; Sari, Arlin Maya (Universitas Pahlawan Tuanku Tambusai, 2024)
This service activity was carried out in the assisted villages of Malikussaleh University, namely Aceh Utara Regency (Payah Gaboh, Reuleut Timu, Reuleut Barat, and Cot Keumuneng Villages), Lhokseumawe City (Blang Pulo, Padang Sakti, Uteun Kot and Lancang Garam Villages). The funeral management training activity (Tajhiz Al-Mayyit) aims to provide education and practice to the community in terms of proper funeral management and following Islamic law. This activity was motivated by several partner problems, namely Lack of knowledge of partners (community) regarding Funeral Management and partners need training in the form of education and assistance to improve skills regarding Funeral Management. The method of implementing the activity consists of 2 stages, namely socialization; in the form of education on funeral management as fardhu kifayah. Workshop in the form of the practice of Funeral Management. This training activity was attended by representatives of each village appointed by their respective villages. The results of this activity can increase people's knowledge and skills regarding the Tajhiz Mayyit process.